Socjologia miasta w Polsce - Malikowski, Marian (Wydział Prawa i Administracji UAM, 1989)
The article is concerned with some aspects and conditions of the present state and prospects of development of the sociology of town in Poland. The reader will find here few comments on particular research trends or the outcome of particular research and more general considerations and evaluations of that sociological subdiscipline made from the contemporary perspective. These evaluations are in general rather critical. Ideological and socio-political conditions of domestic research on town and its social problems have been stressed. The main thesis is that the development of Polish sociology of town needs a definite elimination of all barriers of ideological and political nature (censorship, „taboos", access to some sources, etc.). It also requires more openness and liberalization of scientific policy, e.g. in the sphere of international contacts or as to the need of undertaking research connected with the most pressing social and practical problems of Polish towns. Sociologists who investigate the problems of Polish towns should stay in touch with modern foreign theories and should eventually get rid of some mytfis of ideological nature. Domestic sociology of town needs improvement also in theoretical and methodological planes. Developmental prospects lie in critical analysis, revision and selection as well as in combining and integrating various theoretical and social themes (mostly neomarxist and humanistic). The above would lead to changes in research projects that should more and more often be concerned with municipal policy, planning, municipal social movements, needs and aspirations of townspeople and the possibilities of fulfilling the expectations in town environment i.e. all aspects contributing to the quality of life of townspeople.
The sociology of town in Poland